2007
DOI: 10.1590/s0037-86822007000300008
|View full text |Cite
|
Sign up to set email alerts
|

Soroprevalência da hepatite C em pacientes hemodialisados

Abstract: The objectives of this study were to estimate the serum prevalence of hepatitis C virus (HCV) infection in a dialysis center in the greater Recife region, and to correlate HCV serum positivity with some risk factors. Analyses were performed on 250 patients of both sexes, with ages ranging from 17 to 92 years old. Epidemiological data on these patients were obtained in order to determine the risk factors for this infection. Anti-HCV antibodies were investigated using fourth-generation ELISA. Statistically signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
1
5
0
3
Order By: Relevance
“…This disease should receive constant attention in pregnant women, as infected newborn babies present a high risk of developing chronic forms of the disease due to their immunological immaturity. 24,26,27 The frequency of anti-HCV antibodies found in this study is lower than that reported in the general population, 28,29 but is close to that observed in pregnant women. 30,31 Moreover, pregnant women, with and without seropositivity had similar mean ages.…”
Section: Discussionsupporting
confidence: 58%
“…This disease should receive constant attention in pregnant women, as infected newborn babies present a high risk of developing chronic forms of the disease due to their immunological immaturity. 24,26,27 The frequency of anti-HCV antibodies found in this study is lower than that reported in the general population, 28,29 but is close to that observed in pregnant women. 30,31 Moreover, pregnant women, with and without seropositivity had similar mean ages.…”
Section: Discussionsupporting
confidence: 58%
“…Internacionalmente, a hepatite viral C é responsável por 60% dos casos de doença hepática crônica na Índia (Thakur et al, 2010), bem como em Portugal ocupa o segundo lugar entre as causas de doenças do fígado (Mota et al, 2010). Entre os pacientes de hemodiálise, estudos nacionais apontam uma prevalência de 8,4% (Mello et al, 2007), 13,57% (Sassaki et al, 2006) e 29,1% (Gomes et al, 2006). O controle da contaminação nos sistemas de hemodiálise é rigoroso nas unidades que prestam o serviço, sendo que as estratégias envolvem a desinfecção dos tanques, tubulações e máquinas dialisadoras a partir de métodos físicos (radiação ultravioleta e o aquecimento da água até >80 ºC) ou químicos (ozônio, hipocloritos, formaldeído e ácido paracético) (Jesus & Almeida, 2016).…”
Section: Revista De Gestão Em Sistemas De Saúde -Rgssunclassified
“…Há indicações de que tal contágio possa ocorrer a partir de transfusões sanguíneas e pela transmissão nosocomial, ou seja, transmissão horizontal através do próprio procedimento hemodialítico (Mello et al, 2007). Isso pode ter relação, especialmente, com reúso de dialisadores, contaminação interna das máquinas, contaminação das mãos de membros da equipe e de objetos compartilhados entre os pacientes (Leão;Pace & Chebli, 2010).…”
Section: Revista De Gestão Em Sistemas De Saúde -Rgssunclassified
See 1 more Smart Citation
“…Mello Lde et al [23] , 2007 Lopes et al [24] , 2006 Albuquerque et al [25] , 2005 Carneiro et al [26] , 2001 China Maintain 7.01%-37.34% Ren et al [27] , 2011 Qi et al [28] , 2003 Greece 10%-29% Garinis et al [29] , 1999 Rigopoulou et al [30] , 2005 Sypsa et al [31] , 2005 Sweden 11.0% Almroth et al [32] , 2002 Iran 13.2% Alavian et al [33] , 2003 France 16.3% Salama et al [34] , 2000 Tunisia 19%-41.7% Bouzgarrou et al [35] , 2005 Ayed et al [36] , 2003 Libya 20.5% Daw et al [37] , 2002…”
Section: Risk Factorsmentioning
confidence: 99%